LGG-21. Durability of response to targeted therapies in pediatric low-grade gliomas: A multi-institution retrospective review. (3rd June 2022) - Cantor, Evan; Chaturvedi, Sneha; Reiners, Stephanie; Ogle, Andrea; Meyer, Ashley; Cluster, Andrew; Brossier, Nicole M; Dholaria, Hetal; Govender, Dinisha; Nagabushan, Sumanth; Schwartz, Johnathan; Abdelbaki, Mohamed S; et al.
Abstract: Background: The discovery of the driving oncogenic alterations in pediatric low-grade gliomas (pLGGs) has shifted our focus towards management with targeted therapies, especially in relapsing or progressive disease. Limited data is available on the durability of response to targeted therapy in pLGGs once the therapy has ceased. Methods: Multi-institutional retrospective chart review of patients with pLGGs younger than 25 years, between 2010-2021, was undertaken to evaluate the durability of response to targeted therapy and determine risk factors associated with disease progression after cessation of therapy. Results: Current analysis included 18 patients from two centers. Seven (39%) had neurofibromatosis type-1 (NF-1). Diagnoses included: optic pathway glioma (OPG) (6/18, 33%), pilocytic astrocytoma (8/18, 44%), diffuse fibrillary astrocytoma (1/18), ganglioglioma (1/18), glioneural neoplasm (2/18). Sixteen patients received at least one prior line of chemotherapy (range 1-5). Targeted agents included trametinib (50%), selumetinib (5%), binimetinib (22%), vemurafenib (11%) and everolimus (11%). Median time on therapy was 351 days (range 29-979 days). All, but one patient had residual intracranial findings at the end of therapy: eight patients (44%) had stable disease, while ten required additional therapy; 50% were NF-1 patients with OPG. Median time to progression was 203 days (range 29-615 days). Of those who did not require any additional therapies, 50% had suprasellar tumors. Genomic data was available for twelve patients; BRAF-KIAA1549 fusion was the most common genomic alteration. Others included mutations in KRAS, BRAF (V600E), PTPN11, SOX6-RAF1 fusion, NF-1, and a patient with FGFR1, KMT2C, and PTPN11 alterations. Conclusion: Preliminary analysis demonstrates that despite initial response, the majority of patients required additional line of therapy. Patients with NF-1 and OPGs tend to progress after discontinuing therapy, while suprasellar non-NF1 pLGGs tend to develop sustained response to targeted therapies. Additional multi-institutional analysis is underway and will be presented at the meeting.